Effect of Vitamin C 1.000 mg Intravenous Therapy to Lactate Level, Base Deficit and Central Vein Saturation (SvO2) in Septic Patient - Rahardjo,, Theresia Monica; Redjeki, Ike Sri; Kurniadi, Rudi (Majalah Anestesia dan Critical Care, 2015)
Microvascular endothelial dysfunction is a major problem in sepsis patient, followed by a very high morbidity and mortality rate even optimal effort was done. Vitamin C has ability as antioxidant and can improve endothelial cell function. A prospective, randomized, placebo-controlled, and double blind study was conducted at Intensive Care Unit (ICU) Dr. Hasan Sadikin General Hospital Bandung within 6 months to evaluate the effect of vitamin C 1.000 mg intravenous on lactate level, base deficit and SvO2, in 33 septic patients, aged 17–60 years with acute physiology and chronic health evaluation II (APACHE II) score 15–23. Subjects were divided into two groups, treatment group was given an injection of 5 mL vitamin C 1000 mg and control group had a 5 mL NaCl 0.9% at first to seventh day. Measurement of lactate level, base deficit and SvO2 was done at day 1, day 3, day 5, and day 7. Result showed a significant different lactate level between two groups, a very significant decrease of lactate level and decrease of lactate level percentage occurred in treatment group at day 5. and 7 (p<0.001), a significant decrease of base deficit (p<0.002) and an unsignificant decrease of SvO2 (p>0.05). In conclusion, vitamin C 1.000 mg intravenous can improve lactate level, base deficit and SvO2 in septic patient.